2007
DOI: 10.1007/s11461-007-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the emergence and oviposition of ectoparasitoid Spathius agrili Yang and its host emerald ash borer, Agrilus planipennis Fairmaire

Abstract: Relationships between the emergence and oviposition of ectoparasitoid Spathius agrili Yang and its host emerald ash borer, Agrilus planipennis Fairmaire Abstract Emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae), (= A. marcopoli Obenberger), is an important bark beetle attacking ash trees (Fraxinus spp.). It is very difficult to detect and control because of its highly concealed life history. This pest mainly distributed in partial Asian countries (China, Japan, Korea, Mongolia) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…Previous Þeld studies conducted in northeast China showed that the two larval parasitoids (T. planipennisi and S. agrili) and one egg parasitoid (O. agrili) were the major biotic factors that caused high percentage parasitism (12Ð73%) of immature emerald ash borer larvae or eggs on infested green or velvet ash trees , Wang et al 2007). However, T. planipennisi and O. agrili were primarily found in the northern part of China (Liaoning and Jilin Provinces), while S. agrili was found Ϸ800 km further south in the Tianjian and Beijing areas (in Hebei Province).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous Þeld studies conducted in northeast China showed that the two larval parasitoids (T. planipennisi and S. agrili) and one egg parasitoid (O. agrili) were the major biotic factors that caused high percentage parasitism (12Ð73%) of immature emerald ash borer larvae or eggs on infested green or velvet ash trees , Wang et al 2007). However, T. planipennisi and O. agrili were primarily found in the northern part of China (Liaoning and Jilin Provinces), while S. agrili was found Ϸ800 km further south in the Tianjian and Beijing areas (in Hebei Province).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies found that the three above mentioned Hymenoptera parasitoids inßicted a maximum of 73% mortality to emerald ash borer eggs and/or larvae infesting North American ash trees grown in Chinese plantation or landscapes , Wang et al 2007). These three Chinese parasitoid species have been introduced to the United States for classical biocontrol of emerald ash borer (USDA APHIS 2007, Bauer et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EAB infested trees show no clear symptoms when the infestation is light, and this pest is therefore very difficult to detect and control (Wang et al, in press). Spathius agrili prefers EAB to other Agrilus species and has strong host searching and host finding abilities (Wang and Yang, 2005;Wang et al, 2006). The female wasps not only discover host larvae hidden inside bark and parasitize them successfully, but they also discriminate among host sizes and determine clutch size and progeny sex ratio accordingly (Wang et al, 2008a).…”
Section: Spathius Agrilimentioning
confidence: 99%
“…Previous field studies conducted in the native range of EAB showed that several species of hymenopteran parasitoids were attacking immature stages (eggs and larvae) of EAB in Northeast China Wang et al 2007) and the Russian Far East (Duan 2012a). After safety-testing and regulatory approvals, 3 of these exotic parasitoid species, Spathius agrili Yang (Braconidae), Tetrastichus planipennisi Yang (Eulophidae), and Oobius agrili Zhang & Huang (Encyrtidae), were introduced from China to the U.S. for classical biocontrol of EAB (USDA APHIS 2007; Bauer et al 2008;Duan et al 2010Duan et al , 2012b.…”
Section: Introductionmentioning
confidence: 99%